Social Support System For Children In Government Residential Care Institutions In Pattani, Thailand: Child Caregivers’ Perspectives - Charansarn, Arina (2023)
The purpose of this study was to examine the social support system for children in government residential care in Pattani, Thailand, and to investigate how such sectors associated with the children could indeed enhance potential solutions in the support system to strengthen and improve child wellbeing.